Examination of the Effect of HSG Procedure on Ovarian Surface Epithelium: Experimental Study - Sapmaz, Ekrem; Akpolat, Nusret; Celik, Aygen; Sapmaz, Tansel; Pala, Sehmuz; Hanay, Fethi (Galenos Yayincilik, 2006)
Objective: To examine the effect of lipiodol, tetracycline and radiation used during HSG procedure on ovarian surface epithelium in rats. Material and method: Forty Wistar albino species, adult, female rats that had regular cycles were randomly allocated to 4 groups in the estrus phase. G1: (n=10): The group in which the abdomen was opened and closed without X ray application. G2: (n=10): The group in which the abdomen was opened and closed, and X ray was applied. G3: (n=10): The group in which the abdomen was opened and 0,1 ml. lipiodol was applied to each uterine horn. G4: (n=10): The group in which the abdomen was opened, and 10 mg/kg/ip tetracycline application was followed, after 15 minutes, by 0,1 ml lipiodol application to each uterine horn. After their abdomens were closed, the rats in G2, G3 and G4 were exposed to 3 times whole body radiation with 2-minute intervals (total dose = 5-20 miliRad). The abdomens of all rats were re-opened after 3 hours and left oophorectomy was performed. Samples of left ovaries were fixated in formaldehyde. After the preparations were stained with hematoxylin eosin, stratification, tafting, chromatin irregularity, nuclear contour irregularity, increase in nucleus size, increase in nucleus/cytoplasm rate, pleomorphism, presence of nucleoli, mitosis and hyperchromasia were examined. An ordinal scale was formed for each parameter (none=0 points, slightly present=1 point, present=2 points, markedly present=3 points) and total points of change in ovarian surface epithelium was calculated by adding all. One Way Anova was used in the statistical analysis of data. Tukey HSD test was employed as Post Hoc test and p<0,05 was considered significant. Results: Presence of nucleoli and mitosis values were found similar (p>0,05, Tukey HSD test), but all other parameters (stratification, tafting, chromatin irregularity, nuclear contour irregularity, increase in nucleus size, increase in nucleus/cytoplasm rate, pleomorphism, and hyperchromasia) were significantly higher in G2, when compared to other groups (p<0,05, Tukey, HSD test). The detrimental effect seen in G2 diminishes with lipiodol use and is further reduced by the addition of tetracycline. Conclusion: Use of lipiodol and tetracycline prevents the cancerous effects of radiation on ovarian surface epithelium.
Keywords: lipiodol; ovarian surface epithelium; radiation; rat; tetracycline